(3GdJShjb GdGdcJQhfjs - (3HTjQ(B, (3GdYdGbs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3eONd Gdi GdJShjb GdGdcJQhfj , GdTHcGJ h GSJNOGeGJgG aj GdJShjb , fLGMGJ GdJShjb GdGdcJQhfj , GdeHjYGJ GdGdcJQhfjI , GdNOeGJ GdGdcJQhfjI h CSGdjH JShjbgG , CSGdjH GdJSYjQjI aj HjFI GdCYeGd GdGdcJQhfjI , GdGJUGdGJ GdJShjbjI GdGdcJQhfjI , bfhGJ GdJhRjY aj GdHjFIGdGdcJQhfjIs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdEdcJQhfjs